2016
DOI: 10.1039/c6cp03582e
|View full text |Cite
|
Sign up to set email alerts
|

HP-β-cyclodextrin as an inhibitor of amyloid-β aggregation and toxicity

Abstract: Amyloid deposits of misfolded amyloid-β protein (Aβ) on neuronal cells are a pathological hallmark of Alzheimer's disease (AD). Prevention of the abnormal Aβ aggregation has been considered as a promising therapeutic strategy for AD treatment. To prevent reinventing the wheel, we proposed to search the existing drug database for other diseases to identify potential Aβ inhibitors. Herein, we reported the inhibitory activity of HP-β-cyclodextrin (HP-β-CD), a well-known sugar used in drug delivery, genetic vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 64 publications
1
30
0
2
Order By: Relevance
“…This behavior can lead to increased in vivo ERT release and to the improvement of its bioavailability and activity. In addition, according to the literature [19, 20], an intrinsic activity of HP-betaCD on GAGs restoration also emerges, indicating its potential function in the treatment and prevention of many diseases associated with the imbalance of GAGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior can lead to increased in vivo ERT release and to the improvement of its bioavailability and activity. In addition, according to the literature [19, 20], an intrinsic activity of HP-betaCD on GAGs restoration also emerges, indicating its potential function in the treatment and prevention of many diseases associated with the imbalance of GAGs.…”
Section: Discussionmentioning
confidence: 99%
“…HP-betaCD is a soluble derivative of β -cyclodextrin and was selected because in the literature it is reported that it forms inclusion complexes with flavonoids and enhances their aqueous water solubility and dissolution rate [1618]. Moreover, HP-betaCD appears to be useful in many diseases correlated to an increase of GAGs [19, 20], with PG also involved in OA.…”
Section: Introductionmentioning
confidence: 99%
“…Az amyloid peptidek aggregációjának gátlására több ciklodextrin-féleséget is teszteltek. 14 A leghatékonyabb in vitro aggregáció gátlást -koncentrácófüggõ módon -a hidroxipropil-béta-CD (HPBCD) mutatta. (7. ábra) 7.…”
Section: áBra Egy Terápiás Ciklikus Peptid a Ciklosporin A Szerkezeteunclassified
“…ábra AFM felvételek amyloid beta-peptid aggregációjáról HPBCD jelenlétében 5-10-20 órás inkubáció után. 14 A bíztató in vitro eredményt követõen a Weil Cornell egyetem kutatói igazolták, hogy a HPBCD származék amyloid aggregációt gátló hatása in vivo is jelentkezik. 15 …”
Section: áBra Egy Terápiás Ciklikus Peptid a Ciklosporin A Szerkezeteunclassified
“…Recently, various bioactivities of CyDs have been demonstrated, and CyDs have been used as active pharmaceutical ingredients (APIs) against Niemann-Pick disease type C (NPC), [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] leukemia, 77) hyperlipidemia, 78) Alzheimer's disease, [79][80][81][82][83][84] cerebral ischemic injury, 85) atherosclerosis, 86) diabetic kidney disease, 87) chronic renal failure, 88) AIDS, 89,90) influenza, 91) peripheral artery disease, 92) sterility, [93][94][95] solid cancers, [96][97][98][99][100][101] bacterial growth, 102) α-synucleinopathy, 103) GM1-gangliosidosis, 104) septic shock, [105][106][107] hypervitaminosis, 108) and transthyretin-related familial amyloidotic polyneuropathy (FAP) …”
Section: Cyclodextrin-based Supramolecular Pharmacology and Drug Discmentioning
confidence: 99%